1981
DOI: 10.1002/star.19810330403
|View full text |Cite
|
Sign up to set email alerts
|

Some Properties of Normal‐ and Waxy‐Type Starches of Amaranthus hypochondriacus L

Abstract: Starch granules were prepared from seeds of two types of Amaranthus hypochondriacus L., which are native to Nepal. The perisperm of one type of seeds stained reddish‐brown with iodine solution and that of the other blue. Starch granules had round shape of about 1 μm diameter. X‐ray diffraction diagrams were very similar each other and identical with the corresponding ones of rice and maize starches (A‐type). Amylose contents and distribution of average chain‐lengths of amylopectin were determined by gel filtra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 10 publications
2
24
0
Order By: Relevance
“…Gelatinization profiles of starches of the grain amaranths (Figs. 5a 1-5) are very similar to those reported by Kainuma et al (17) for fine starch granules such as those of Saponaria vaccaria as described earlier (2). Starches of A. caudatus #76325 exhibited the lowest temperature for initiation of gelatinization (Figs.…”
Section: Absorption Spectra Of Starch-iodine Complexessupporting
confidence: 87%
See 4 more Smart Citations
“…Gelatinization profiles of starches of the grain amaranths (Figs. 5a 1-5) are very similar to those reported by Kainuma et al (17) for fine starch granules such as those of Saponaria vaccaria as described earlier (2). Starches of A. caudatus #76325 exhibited the lowest temperature for initiation of gelatinization (Figs.…”
Section: Absorption Spectra Of Starch-iodine Complexessupporting
confidence: 87%
“…DISCUSSION We confirmed that there are both normal and waxy-types in the same species of Amaranthaceae, A. hypochondriacus L., by the investigation of properties of starches isolated from the seeds (Table 1). Starch granules of A. hypochondriacus #76338-2 consist of nearly 100% typical amylopectin the same as those of #76343-1 reported previously (2). The widespread distribution of starches staining red with iodine has been recognized for the past century (1).…”
Section: Elution Profiles Of Isoamylase-debranched Starches By Gel Fisupporting
confidence: 60%
See 3 more Smart Citations